2021
DOI: 10.1186/s12879-021-06110-x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of modified HIV and antiretroviral drug testing using self-collected dried blood spots from men who have sex with men

Abstract: Background In the US, one in six men who have sex with men (MSM) with HIV are unaware of their HIV infection. In certain circumstances, access to HIV testing and viral load (VL) monitoring is challenging. The objective of this study was to evaluate the feasibility of conducting laboratory-based HIV and antiretroviral (ARV) drug testing, and VL monitoring as part of two studies on self-collected dried blood spots (DBS). Methods Participants were ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Therefore, this high rate of success in DBS collection may not occur in the general population. Similar studies using at-home self-collected DBS reported lower return rates than this study ( 10 , 14 16 ) but the proportion of samples that were unsuitable for testing upon arriving at the lab were comparable ( 14 16 ). It is of note that while our study demonstrates an effective use of self-collected DBS as a sample type, rather than more invasive and labor-intensive plasma and serum samples, the test still requires trained laboratory staff, specialized equipment, and time to perform.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, this high rate of success in DBS collection may not occur in the general population. Similar studies using at-home self-collected DBS reported lower return rates than this study ( 10 , 14 16 ) but the proportion of samples that were unsuitable for testing upon arriving at the lab were comparable ( 14 16 ). It is of note that while our study demonstrates an effective use of self-collected DBS as a sample type, rather than more invasive and labor-intensive plasma and serum samples, the test still requires trained laboratory staff, specialized equipment, and time to perform.…”
Section: Discussionsupporting
confidence: 62%
“…Self-sampling devices for dried blood spots (DBS) are feasible in this population such that participants describe this approach as convenient because it eliminates the need for in-person venipuncture (8,9). In fact, self-sampling of DBS for laboratory-based VL testing is a medically effective measure to reduce AIDS-related mortality in Africa, and has contributed to the surveillance of HIV drug resistance (10)(11)(12). Although it has the potential to optimize HIV treatment as prevention, further research is needed to optimize procedures for implementing self-sampling of DBS in high priority populations with HIV such as people who use stimulants.…”
Section: Introductionmentioning
confidence: 99%